Thanatology and Economics: The Behavioral Economics of Death - Slemrod, Joel (American Economic Review, 2003)
Death is an integral part of life. Yet the economic modeling of death is perfunctory, with most of the controversy focused on whether people's planning horizon ends with their own life or extends beyond that. In contrast, one might expect that, of all aspects of life, decisions that require facing up to one's own mortality engender unique fears and psychological reactions.1 That we are forwardlooking and can anticipate death distinguishes human beings from other species. Sigmund Freud's student Otto Rank (1941) argued that mortality anxiety was the fundamental human fear, and he attributed the genesis of man's religious impulses and the source of humanity's construction of meaning and order to the awareness of one's personal finitude. Rank's ideas were revived and popularized in Ernest Becker's (1973) book The Denial of Death. The idea that many people live in denial of their own mortality is common in literature and philosophy, perhaps best summarized in the words of the 17th-century French epigrammist Francois La Rochefoucauld: One cannot look directly at either the sun or Many central issues in economics, such as the intertemporal pattern of consumption, are at stake if people systematically deviate from the predictions of standard models with regard to decisions concerning their own death. Assessing whether this is true requires enriching the models of how people behave in the face of death and testing them against observed patterns of behavior.